2022
DOI: 10.2174/1570159x19666211101111430
|View full text |Cite
|
Sign up to set email alerts
|

Transgenerational Abnormalities Induced by Paternal Preconceptual Alcohol Drinking: Findings from Humans and Animal Models

Abstract: : Alcohol consumption during pregnancy and lactation is a widespread preventable cause of neurodevelopmental impairment in newborns. While the harmful effects of gestational alcohol use have been well documented, only recently the role of paternal preconceptual alcohol consumption (PPAC) prior to copulating has drawn specific epigenetic considerations. Solid human and animal model data demonstrated that PPAC may affect sperm function eliciting oxidative stress. In newborns, PPAC may induce changes in the behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 203 publications
1
17
0
Order By: Relevance
“…Recent evidence demonstrated that resveratrol mediates epigenetic changes (methylation and acetylation) that persist across generations and that are involved in aging and the function of the nervous system [ 168 , 169 , 170 , 171 ]. The study of key markers involved in senescence and rejuvenation (mitochondrial biogenesis and Sirt1-AMPK-PGC1-α) demonstrated that resveratrol is also able to modulate the changes in these cellular metabolic pathways.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…Recent evidence demonstrated that resveratrol mediates epigenetic changes (methylation and acetylation) that persist across generations and that are involved in aging and the function of the nervous system [ 168 , 169 , 170 , 171 ]. The study of key markers involved in senescence and rejuvenation (mitochondrial biogenesis and Sirt1-AMPK-PGC1-α) demonstrated that resveratrol is also able to modulate the changes in these cellular metabolic pathways.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…The advice was originally that ‘… attention should be given to […] prevention of drinking among pregnant women and women of childbearing age’ but this was swiftly amended after a public outcry and now only speaks about pregnant women ( WHO, 2021 ). While it is legitimate to inform women and men that alcohol consumption can have a negative impact on fertility and reproductive outcomes, it is quite a leap to argue that all women, but not men, of childbearing age should avoid alcohol since the advice is: (i) not well targeted (as not all women of childbearing age plan to ‘bear children’), (ii) paternalistic (as it does not aim to enable better informed decision-making regarding alcohol intake, but to stop young women from consuming alcohol), (iii) overreaching (as complete prevention is not necessary to avoid negative impacts), and (iv) disproportionately focused on women (as preconception alcohol intake by men is also associated with worse perinatal outcomes, see, for example, Terracina et al , 2022 ). Unfortunate missteps like these contribute to a climate in which beneficial fertility health messages may also be rejected because they are perceived as offensive, discriminating or overly paternalistic.…”
Section: Introductionmentioning
confidence: 99%
“…Alcohol abuse may result in significant mental [ 4 , 5 , 6 , 7 , 8 ] or physical health problems [ 9 , 10 , 11 , 12 ]. Furthermore, when consumed during gestation, it may induce severe damage to the newborns [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. Alcohol is a well-known carcinogen compound but it is still underestimated in the general population, partially also because of the alcohol industry’s extensive misrepresentation of evidence about the alcohol-related risk of cancer [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%